Software development with grammatical approach - Kosar, Tomaž (Informatica (Ljubljana), 2004)
The paper presents a grammatical approach to software development. It supports formal software specification using attribute grammars, from which a rapid prototype can be generated, as well as the incremental software development. Domain concepts and relationships among them have to be identified from a problem statement and represented as a con text-free grammar. The obtained con text-free grammar describes the syntax of a domain-specific language whose semantics is the same as the functionality of the system under implementation. The semantics of this language is then described using attribute grammars from which a compiler is automatically generated. The execution of a particular program written in that domain-specific language corresponds to the execution of a prototype of the system on a particular use case.
Keywords: informatika; information science; načrtovanje programske opreme; modeliranje; slovnica; grammar